Thermoregulatory responses during prolonged swimming with a Wetsuit at 25 °C - Rois, S.; Zacharakis, E.; Kounalakis, S.; Soultanakis, H. N. (International Journal of Performance Analysis in Sport, 2021)
The aim of this study was to investigate the effect of prolonged steady state swimming with a wetsuit, on thermoregulatory and behavioural responses, in water of 25°C. Ten male swimmers participated in two 75-min swim trials, in one wearing a neoprene wetsuit (WS), and the other a conventional swimsuit (SS). The swimming intensity was controlled at 70% of swimmers` critical velocity (CV). Core (Tcore) and skin (Tsk) temperature, heart rate (HR), and behavioural modulators, were measured before, during and after swimming. A 2-way ANOVA for repeated measures with aFisher`s 2SD test was used for multiple comparisons and a paired t-test with a Tukey post hoc analysis for pre and post measurements at p< 0.05. The results demonstrated an interaction of Tcore (p = 0.039), between time in the water and type of garment worn. Tcore with the WS initially increased until the 45th min and plateaued, while with the SS was continuously decreasing. HR was lower during swimming with the WS and higher with the SS. Thermal sensation and thermal comfort, were more favourable with the WS (p < 0.05). Thus, WS use during prolonged swimming, helped maintain Tcore levels, and improved thermal perceptions, at 25 °C.